Unveiling the Strategy Behind Blackfishing: Kim Kardashian's Instagram and the New Beauty Discourse - Breda Mukti Lukitasari; Asri Saraswati (Jurnal Syntax Admiration, 2024)
As a fashion and beauty icon in America, Kim Kardashian is one of the public figures who supports the new beauty discourse. The emerging concept of new beauty in America challenges conventional limits for the delineation of beauty. This idea emphasizes that beauty is not limited by skin color, body shape, age, and hairstyle; instead, it emphasizes the need of embracing of natural body. This study examines how Kim Kardashian's personal Instagram posts from 2014-2023 showcases new notions of beauty via the lens of semiotic theory by Barthes (1964) and the concept of blackfishing. New forms of beauty discourse displayed by Kim Kardashian are accused of being blackfishing by excessively darkened skin, curvy body shapes, full lips, and hair. According to the findings of this study, there is a sense of ambivalence towards black women's bodies. Consequently, white people have internalized certain characteristics of black bodies without appreciating the unique qualities of black women. Kim Kardashian promotes a new beauty discourse that is considered blackfishing through her collaboration with the fashion and beauty industry and building her own cosmetics business. This demonstrates the participation of other influential individuals in the fashion business who endorse Kim's blackfishing appearance so that this appearance continues to appear in public and is normalized.